Towards the Tree Automata Workbench Marbles - Drewes, Frank (Electronic Communications of the EASST, 2010)
The conceptual ideas that are intended to become the basis for the tree automata workbench Marbles are sketched. The goal is to design and implement an extensible system that facilitates experiments with virtually any kind of algorithm on tree automata. Moreover, the system will be released with a library and an application programmer’s interface to make it accessible to anyone who wants to apply tree automata algorithms in research and development.